(untitled) (Bangladesh Journal of Animal Science, 2013)
A study was conducted to determine the meat yield characteristics of Khaki Campbell, Jinding and Deshi duck in two coastal locations of Barisal and Bhola districts of Bangladesh. Sixty day-old ducklings of three genotypes of duck were randomly allocated to 3 treatments having 4 replications in each genotype. Ducklings are reared up to 150 days and at the end of experiment, one male duck of highest live weight was selected from each replication in the morning before feeding and dissected to determine the meat yield characteristics. Significant (p<0.01) differences were found between different genotypes in carcass weight and dressed weight of ducks. Significant (p<0.01) differences were also observed for weight of breast, thigh, leg, shank and drumstick weight as well as dressing percentage. Dressed weight and dressing percentage in Khaki Campbell was significantly (p<0.01) higher than that of the Jinding and Deshi genotypes. Considering the parameters studied both Khaki Campbell and Jinding ducks may be suggested to rear in the coastal region of Bangladesh. DOI: http://dx.doi.org/10.3329/bjas.v41i2.14121 Bang. J. Anim. Sci. 2012. 41 (2): 79-82